The role of the molecular pathway of transforming growth factor β in the progression of myocardial fibrosis - A. S. Sinyaeva; S. A. Shcherbakova (Klinicist)
To date, the consequences of progressive myocardial fibrosis are an urgent problem. Fibrosis is the basis for the progression of many cardiovascular diseases and leads to structural remodeling of the myocardium. Fibrosis isolates groups of cardiomyocytes and individual cells, disrupts the connection between them, which causes rhythm disturbances, including the development of atrial fibrillation. Fibrosis is the result of pathological remodeling in many tissues and contributes to the development of clinical diseases. At the moment, it is of great interest to identify means of slowing down and stopping the progression of tissue fibrogenesis. The progression of myocardial fibrosis is based on mechanisms that are associated with both cellular and molecular pathways. The main cellular element is an activated fibroblast, which produces a large amount of extracellular matrix. One of the main molecular mechanisms are transforming growth factor β, platelet-derived growth factor, connective tissue growth factor, vasoactive compounds (angiotensin II), cytokine-induced extracellular matrix pathways. It is these elements of the pathogenesis of the disease that can become the objects of new therapeutic interventions. This review article will present data on the prevalence and frequency of visits to medical institutions on issues related to developed gastric arrhythmias against the background of interstitial fibrosis, on the molecular processes involved in the initiation of myocardial fibrosis, as well as on non-coding RNAs regulating specific cellular signals, and on the studied therapeutic drugs inhibiting the transforming growth factor β signaling pathway. Generalized and structured information will help expand the understanding of molecular processes and, in the future, change approaches to the treatment of many heart diseases.